Prevalence of Obstetric Fistula and Associated Factors in Rajasthan, India. (June 2019) - Singh, J. P.; Gupta, S. D.; Khanna, Anoop; Sharma, Laxman Swaroop
Context: Obstetric fistula is a serious obstetric and social morbidity among women. Reliable data on incidence and prevalence of obstetric fistula are not available. Aims: The present study attempted to measure the prevalence of obstetric fistula and evaluate factors associated with it. Settings and design: Study was conducted in Rajasthan, India. The cross-sectional data were used for estimation of prevalence of obstetric fistula, while the case comparison design was used to identify the risk factors associated with obstetric fistula. Methods and material: A cross-sectional population-based district level survey covered 41, 448 ever married women of age group 15–49 years in 40, 052 randomly selected households. Statistical analysis used: To explore association between various identified demographic, social, economic, service delivery and utilization variables and obstetric fistula, simple and multivariate logistic regression was performed. Results: The estimated prevalence of obstetric fistula was 4 per 1, 000 women. About 85 per cent of the women with fistula were married below 18 years of age, and 48 per cent gave birth to the first child before 20 years of age. The risk of developing obstetric fistula was more than twice among women who experienced obstructed labour, the adjusted odds ratio being 2.21 (95% Confidence Interval (CI) 1.12 −4.80). Conclusions: Obstructed labour was most prominent obstetric risk factor for obstetric fistula. The other risk factors were early marriage and early child birth. Ironically, obstetric fistula is preventable by improving quality of maternal care and effective emergency obstetric care. Education and communication can play an important role in postponement of early marriages and early child birth.